Optimization of Cost Analysis in School Construction: Risk Management. - Andres, Wilder (2023)
This paper proposes to optimize the conventional cost analysis used by SMEs in school construction through qualitative analysis using Primavera Risk Analysis, Microsoft Excel, and Primavera P6. Several stages were carried out during the process: risk identification, identification of the most sensitive and susceptible items to project changes, sensitivity analysis, criticality analysis, all represented in tornado, bar, and scatter plots. The proposed risk management plan yielded the following results: it increased the reliability of the project's completion date from 41% to 61% in the analysis, increased budget reliability from 29% to 45%, and reduced the number of sensitive items based on 1000 iterations.